Far from the core - regions and industrial parks in economic shadow in Hungary (Part two) - Tiner, Tibor (Hungarian Geographical Bulletin, 2010)
The first part of the paper (Hung. Geogr. Bull. No 2. 2010) was an attempt to evaluate the level of development of NUTS2 regions of the country on the basis of data for the leading 500 companies. The main results of the analysis showed close correlation between the geographical position and success (or failure) in business. The second part of the paper deals with economic efficiency of top firms that are settled into industrial parks of modestly developed and less favoured counties. Analyses were carried on using financial and statistical indicators published by different institutions and firms (e.g. Central Statistical Office, Creditreform Ltd.) electronically or in printed version. The conclusion of the study is that the economic crisis burst in 2008 has affected adversely both the annual revenues and profits of the top firms settled into industrial parks of the counties mentioned above.